Polyclonal activation of human peripheral blood B lymphocytes by Fusobacterium nucleatum. - Mangan, D F (1983)
The present study examined in vitro polyclonal human B-lymphocyte (B-cell) activation (PBA) by Fusobacterium nucleatum. Pokeweed mitogen, a well-studied PBA activator, was included in some experiments for comparison. PBA was determined by the total immunoglobulin A, G, and M concentrations in the culture supernatants as measured by micro-enzyme-linked immunosorbent assay. F. nucleatum, at concentrations between 1 and 10 micrograms/ml, stimulated optimal PBA in monocyte-depleted cultures, whereas the pokeweed mitogen response was optimal in unfractionated, monocyte-containing cultures. Immunoglobulin synthesis occurred primarily between days 6 and 8 after stimulation with F. nucleatum. T lymphocytes enhanced the PBA response to F. nucleatum, particularly at a T- to B-cell ratio of 1:1. Immunoglobulin production was greater in round-bottomed wells than in flat-bottomed wells at lymphocyte concentrations of 200,000 cells per well. The PBA response, however, increased dramatically in flat-bottomed wells containing higher lymphocyte concentrations, suggesting that PBA is enhanced by cell-to-cell contact. A delay in stimulation of the lymphocytes with F. nucleatum resulted in diminished immunoglobulin production. The results provide information on the regulation of in vitro PBA induced by F. nucleatum. The data also suggest that there may be differences in the mechanisms by which F. nucleatum and pokeweed mitogen stimulate PBA.